Respuesta :

Answer:

[tex]y = -\frac{4}{3} x - 1[/tex]

Step-by-step explanation:

y = mx + b

m = delta y / delta x

m = (-13 - 3) / [(9 - (-3)]

m = -16/12

m = -4/3

From (-3 | 3) we know that when x = -3, y = 3

Placing into equation to find b

3 = (-4/3)*-3 + b

3 = 12/3 + b  

b = -1

The equation of the line that passes through the given points is 3y + 4x = -3

From the question,

We are to determine the equation of the line that passes through the points (-3,3) and (9,-13)

The equation can be determined by using the formula for calculating the equation of a line with two given points.

The formula for determining the equation of a straight line with two given points (x₁, y₁) and (x₂, y₂) is

[tex]\frac{y-y_{1} }{x-x_{1} } = \frac{y_{2} -y_{1} }{x_{2} -x_{1} }[/tex]

From the question,

x₁ = -3

y₁ = 3

x₂ = 9

y₂ = -13

Putting the parameters into the formula, we get

[tex]\frac{y-3}{x--3}= \frac{-13-3}{9--3}[/tex]

This becomes

[tex]\frac{y-3}{x+3} = \frac{-16}{12}\\[/tex]

Then,

[tex]\frac{y-3}{x+3}=\frac{-4}{3}[/tex]

This becomes

[tex]3(y-3) = -4(x+3)[/tex]

Clearing the brackets, we get

[tex]3y -9 = -4x -12[/tex]

[tex]3y+4x= -12 +9[/tex]

[tex]3y +4x =-3[/tex]

Hence, the equation of the line that passes through the given points is 3y + 4x = -3

Learn more here: https://brainly.com/question/18643171

ACCESS MORE